2009
DOI: 10.1002/bdm.661
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between indecisiveness and eye movement patterns in a decision making informational search task

Abstract: Indecisiveness is a trait-related general tendency to experience decision difficulties across a variety of situations, leading to decision delay, worry, and regret. Indecisiveness is proposed (Rassin, 2007) to be associated with an increase in desire for information acquisition and reliance on compensatory strategies-as evidenced by alternative-based information search-during decision making. However existing studies provide conflicting findings. We conducted an information board study of indecisiveness, using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 28 publications
2
28
0
1
Order By: Relevance
“…To capture these process measures, a method that can be used in future menu labeling studies is eye tracking. Using this method, eye fixation locations and durations are recorded while individuals scan information on a screen, or in this case, a menu (Patalano, Juhasz, & Dicke, 2010). This eye tracking method simulates natural information search (Lohse & Johnson, 1996) and could capture consumers' natural ordering behavior.…”
Section: Discussionmentioning
confidence: 99%
“…To capture these process measures, a method that can be used in future menu labeling studies is eye tracking. Using this method, eye fixation locations and durations are recorded while individuals scan information on a screen, or in this case, a menu (Patalano, Juhasz, & Dicke, 2010). This eye tracking method simulates natural information search (Lohse & Johnson, 1996) and could capture consumers' natural ordering behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, student samples may be acceptable when relationships between constructs and not absolute magnitudes are of interest for the researcher (Reynolds et al, 2003;Demirbag et al, 2010). The use of students in our research is further justified by the growing interest in understanding the new and demographically dominant generation of young consumers in emerging economies, and by the use of timeconsuming eye-tracking technology that demands smaller sample sizes in order to be economically feasible (compare Wedel and Pieters, 2000;Patalano et al, 2010). Participants did not receive remuneration for their participation in the study.…”
Section: Methods Participantsmentioning
confidence: 97%
“…The limitations in sample size and representativeness in this research are due to timeconsuming and cost-intensive research procedures when using eye-tracking methodology. Although eye-tracking studies frequently employ small sample sizes (for example, Wedel and Pieters, 2000;Patalano et al, 2010), a larger sample would be desirable in order to gain precision in the statistical analyses and increase the generalizability of the findings. Specifically, Hair et al (2014) suggest that in order to detect an R 2 of 0.10 with a statistical power of 80 per cent at the 5 per cent significance level, a sample size of 110 is needed for PLS-SEM, which is above our sample of 81 participants in this study.…”
Section: Limitations and Further Researchmentioning
confidence: 99%
“…For example, advances in eye-tracking are identified as making this methodology especially well suited to understanding shopper decision-making (Patalano, Juhasz, & Dicke, 2010), particularly in the retail setting (Harwood & Jones, 2014;Shankar et al, 2011). Chandon et al (2006, p. 6) observed that "eye-tracking data provide reliable measures of attention to stimuli in complex scenes, such as brands on a supermarket shelf."…”
Section: Introductionmentioning
confidence: 97%